Catalytic Reforming of n-Heptane by Pt-Cu Supported on g-Alumina - Vadi, Mehdi; Amin Mozafaripoor, M. (Asian Journal of Chemistry, 2010)
A two-metal catalyst was prepared by means of impregnation from the solutions which have Cu(NO3)2·3H2O and H2PtCl6·xH2O and 1 mL of HCl (0.1 M). The activity and selectivity of this catalyst to examine on the n-heptane with the following experimental conditions; temperature: 450-510 ºC, pressure: 15-30 atmosphere and the ratio of the reagents under laboratory circumstances. The n-heptane is converted to the branched aliphatic isomers and aromatics. This catalyst has high selectivity and ability to do the aromatic reactions and in converting the n-heptane by using this catalyst, a little amount of cracking interaction products have been produced. According to the tests copper can improve the acidic feature of which itself increases the selectivity to aromatics and decreases the cracking.